Au(I)-Catalyzed Ring Expanding Cycloisomerizations: Total Synthesis of Ventricosene - Sethofer, Steven G. (2008)
[Image: see text] The gold(I)-catalyzed cycloisomerization of enynes containing an embedded cyclopropane unit leads selectively to the formation of ring systems containing the cyclopropylmethyl cation. A subsequent Wagner–Merwein shift provides diastereomerically pure fused cyclobutanes. The utility of this methodology for the rapid assembly of polycyclic ring systems is illustrated by the total synthesis of the angular triquinane ventricosene.